Mathematical model for the recovery of gold and zinc through the flotation process from marmatic zinc sulfured minerals in the province of Casma – Ancash - Aramburú Rojas, Vidal Sixto (2022)
The present research study demonstrates that the recovery of gold and zinc in gold-containing marmatitic zinc ores is feasible. The recovery of these metals was analyzed by factorial experimental designs, using the reagents: CuSO4, AR-3418 and AR-1242 as independent variables, while all other variables remained constant. As a result of the research, a mathematical model was obtained for the recovery of gold and zinc, performing the adjusted factorial design analysis, as indicated: Recovery of gold (Au) = 83.40+ 0.00600 CuSO4 + 0.110 AR-3418 + 0.035 AR-1242 + 0.000313 CuSO4 * AR 3418+ 0.000275 CuSO4 * AR-1242- 0.00800 AR-3418 * AR-1242 - 0.000011 CuSO4 * AR-3418 * AR-1242. Likewise, the recovery of zinc (Zn) = 73.14 + 0.0100 CuSO4 + 0.132 AR-3418 + 0.051 AR-1242 + 0.000164 CuSO4 * AR-3418 + 0.000131 CuSO4 * AR-1242 - 0.00811 AR-3418 * AR-1242 - 0.000004 CuSO4 * AR-3418 * AR-1242.